Perancangan Sistem Informasi Akuntansi Aset Tetap Dengan Metode Garis Lurus Sebagai Perhitungan Penyusutan Aset Tetap - Eni Endaryati; Vivi Kumalasari Subroto (Universitas Sains dan Teknologi Komputer, 2020)
Fixed assets are tangible assets that are owned for use in the production or supply of goods or services, for rent to other parties, or for administrative purposes and are expected to be used for more than one period. Due to its high value, relatively long use and being the company's main tool to generate revenue, investment in fixed assets (Capital Budgeting) must be carefully calculated. In addition, depreciation or depreciation is the allocation of the cost of a fixed asset which is the effect of the decline in the value of the fixed asset. The reason why many companies apply the straight line method of depreciation (Straight Line Method) is because there are relatively stable maintenance and repair costs in each period, and the costs are not affected by productivity or are not affected by deviations. Therefore, the assets owned must continue to be managed properly so that companies and individuals can benefit from the existence of these assets, especially fixed assets. But this is not the case with KSP Mandiri Sejahtera Semarang where fixed assets have not been well managed. This results in inconsistencies and calculation errors, incomplete data, which results in inappropriate decision making and the value of the company's fixed assets has not been recorded properly and accurately. With a new structured management system where the calculation and reporting of depreciation of fixed assets using the straight-line depreciation method helps the calculation of depreciation of fixed assets owned by the company, besides that it also provides information about the detailed condition of each fixed asset owned by the company so that it helps the company manage its fixed assets , as well as helping to present accurate and accurate reports for the benefit of the company's internal financial reports and taxation.